Srovnávací reklama v ČR a v zahraničí - Kurzok, Adam; Večerková, Eva, 1958-; Masarykova univerzita. Katedra obchodního práva (2006)
The diploma thesis with the title - Comparative advertising in the Czech republic and foreign countries is focused in 20 000 words mainly on domain of unfair competition and comparative advertising in the Czech republic and takes a detailed view on current legal status, being seen in the Czech commercial law act nr. 513/1991, as well as points out some legal inaccuracies in implementing the Directive 84/450/EEC concerning misleading and comparative advertising and makes the suggestions about prospect legal amendments.
Vedoucí práce: Eva Večerková.
Diplomová práce (Mgr.)--Masarykova univerzita, Právnická fakulta, 2006.
Keywords: reklama a propagace; srovnávací reklama; advertising; comparative advertising; diplomové práce; master's theses